2017
DOI: 10.1021/acssuschemeng.7b02465
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Immobilization of Laccase onto Nanofibrous Membrane for Degradation of Pharmaceutical Residues in Water

Abstract: Enzymatic degradation with ligninolytic enzyme e.g. laccase is a potential green solution for removal of pharmaceutical compounds that are released into the environment through wastewater effluent. However, the deficiencies of using the enzyme in its free forms, such as reusability and stability should be addressed before industrial applications. In this study, laccase was immobilized onto tailor-made Polyacrylonitrile-biochar composite nanofibrous membrane through covalent bonding and the parameters of immobi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 42 publications
1
38
0
1
Order By: Relevance
“…For laccases it was shown that a covalent grafting via a crosslinking agent such as glutaraldehyde is very efficient. Immobilization support materials like ceramic mono or multichannel membranes [19,20], nano-fibrous membranes [21], metal nanoparticles [22], carbon nanotubes [23] and mesoporous materials [24], magnetic cross-linked enzyme aggregates (M-CLEAs) [25] have successfully demonstrated the immobilization of laccase for the degradation of antibiotics. However, many of these materials present a limited surface area available for grafting; this is especially the case of membranes.…”
Section: Introductionmentioning
confidence: 99%
“…For laccases it was shown that a covalent grafting via a crosslinking agent such as glutaraldehyde is very efficient. Immobilization support materials like ceramic mono or multichannel membranes [19,20], nano-fibrous membranes [21], metal nanoparticles [22], carbon nanotubes [23] and mesoporous materials [24], magnetic cross-linked enzyme aggregates (M-CLEAs) [25] have successfully demonstrated the immobilization of laccase for the degradation of antibiotics. However, many of these materials present a limited surface area available for grafting; this is especially the case of membranes.…”
Section: Introductionmentioning
confidence: 99%
“…reported the covalent immobilization of Trametes versicolor laccase on a nanofibrous membrane applied to the degradation of the pharmaceuticals diclofenac, chlortetracycline and carbamazepine. Degradation efficiencies of 72.7%, 63.3% and 48.6%, respectively, were obtained after 8 h of the reaction . These results demonstrate the great capacity for degradation presented by systems with immobilized enzymes.…”
Section: Polymer Supports For Degradation Of Organic Pollutantsmentioning
confidence: 58%
“…Degradation efficiencies of 72.7%, 63.3% and 48.6%, respectively, were obtained after 8 h of the reaction. 118 These results demonstrate the great capacity for degradation presented by systems with immobilized enzymes. In addition, when comparing the degradation performed by the free enzyme with the immobilized enzyme, the immobilized enzyme was shown to work more efficiently and over a wider range of conditions.…”
Section: Crosslinkingmentioning
confidence: 76%
“…It showed high oxidation potential (265% that of the free enzyme), and retained the residual enzyme efficiency of up to 84.6% under repeated batch conditions of 10 cycles [108] Chitosan crosslinked with genipin Improved pH, thermal, and storage stabilities of when compared with the free counterpart. The chitosan laccase system exhibited a residual activity of >55% after 11 cycles [109] polyacrylonitrile-biochar composite nanofibrous membrane High conversion for after 8 h of reaction [110] Table 3. Cont.…”
Section: Immobilization System Results Referencementioning
confidence: 99%